The goats - Cole, Brock (New York : Farrar, Straus and Giroux, 1987)
Stripped and marooned on a small island by their fellow campers, a boy and a girl form an uneasy bond that grows into a deep friendship when they decide to run away and disappear without a trace.
Notable/Best Books (A.L.A.).
Wilson's Children.
Wilson's Junior High School.
5.8
6.3
5-8.
Keywords: Camps -- Fiction; Friendship -- Fiction; Runaways -- Fiction; Survival -- Fiction; Camps -- Fiction; Friendship -- Fiction; Runaway children -- Fiction; Survival skills -- Fiction